2018
DOI: 10.1159/000495865
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of VCP-Interacting Membrane Selenoprotein (VIMP) Leads to G1 Cell Cycle Arrest and Cell Death in MIN6 Insulinoma Cells

Abstract: Background/Aims: VCP-interacting membrane selenoprotein (VIMP), an ER resident selenoprotein, is highly expressed in β-cells, however, the role of VIMP in β-cells has not been characterized. In this study, we studied the relationship between VIMP deficiency and β-cell survival in MIN6 insulinoma cells. Methods: To determine the role of VIMP in β-cells, lentiviral VIMP shRNAs were used to knock down (KD) expression of VIMP in MIN6 cells. Cell death was quantified by propidium iodide (PI) staining followed by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…It has been reported that SelS are involved in various cells survival during ER stress and oxidative stress (Lee et al 2015, Men et al 2018a. Consistent with these results, we also found that SelS deficiency induced an augmentation in 3T3-L1 adipocyte apoptosis after induction of differentiation by disruption of the IRE1α-XBP1 pathway, which was associated with an…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that SelS are involved in various cells survival during ER stress and oxidative stress (Lee et al 2015, Men et al 2018a. Consistent with these results, we also found that SelS deficiency induced an augmentation in 3T3-L1 adipocyte apoptosis after induction of differentiation by disruption of the IRE1α-XBP1 pathway, which was associated with an…”
Section: Discussionsupporting
confidence: 91%
“…Control and SelS KD 3T3-L1 cells after induction for 12, 20, 24, and 28 h were harvested, cell cycle was analysed by flow cytometry as previously reported (Men et al 2018a).…”
Section: Analysis Of Cell Cycle Distributionmentioning
confidence: 99%
“…SELENOK was found to have a crucial role in the proliferation and activation of immune cells and the promotion of calcium flux that induces melanoma progression [14]. SELENOS was found to be highly expressed in insulinoma cells, and its silencing is able to induce apoptosis by decreasing Bcl-xL in β-cells and to block the cell cycle by downregulating the transcription factor E2F1 and increasing cyclin dependent kinase inhibitor p27 expression [15].…”
Section: Introductionmentioning
confidence: 99%
“…This gene joins the regulation of iron homeostasis and inflammatory responses. Men et al 37 found that VIMP/ SELENOS was associated with cell death and the cell cycle in insulinoma cells. However, there have been few studies on these genes in OV.…”
Section: Discussionmentioning
confidence: 99%